Determinants of financial well-being among young employees in Peninsular Malaysia - Zakaria, Nurul Farhana (2014)
Current high levels of individual indebtedness and increasing focus on individual responsibility for financial planning shows that there is a growing need for better financial management particularly among the young adults. Today’s young adults are confront with the complexity of financial products in the market, thus increased their role in managing their finances. The purpose of this study is to examine the erminants of financial well-being among young employees in central region,Peninsular Malaysia. There are four objectives in this study: (1) to identify the levels of financial literacy, money attitude, financial strain, financial capability and financial well-being of young employees; (2) to explore the differences in financial well-being based on demographic characteristics of young employees; (3) to analyze the relationships between financial literacy, type of money attitude, financial strain and financial capability with the financial well-being of young employees and (4) to identify the determinants of financial well-being among young employees. The sample consisted of 508 of young employees in both public and private agency aged 40 years and below from four states of central region in Peninsular Malaysia,which was selected through multi stage sampling technique. Data were collected through self-administered questionnaires. Descriptive and inferential analysis of correlation, independent sample t-test, Analysis of Variance (ANOVA) and multiple regression were used using the Statistical Software Package for Social Science (SPSS). Findings indicated that 290 (57.1%) of the respondents were represented for public agency and the remaining 218 (42.9%) were from private agency. Most of the respondents represented high-income group with mean household income of RM4,937.66 and had tertiary education level. Findings also indicated that the respondents had moderate levels of financial literacy, financial capability and financial well-being, scored high in effort and retention of money attitude and had low level of financial strain. Results of independent sample t-test showed there was a significant difference in financial well-being between gender (male and female) and marital status (married and single) while ANOVA revealed there was a significant difference between high-income group with lower and middle-income group. Pearson Correlation indicated that there were positive significant correlations between financial literacy, type of money attitude and financial capability with financial well-being while there was negative significant correlation between financial strain with financial well-being. The regression analysis showed that variables used in this study contributed 40.8% to the model. There were influences of demographic characteristics (gender and monthly household income) toward financial well-being of young employees. Financial literacy, retention-money attitude, effort-money attitude, financial strain and financial capability had significant influence toward financial well-being whereby financial strain become a major contributing factor to financial well-being. This study suggests that the findings are useful to the government to make an inclusive approach especially to the lower-household income group of young employees to improve the standard of living and enhance their financial well-being while Non-Governmental Organizations (NGOs) such as Federation of Malaysian Consumers Associations (FOMCA) and Credit Counseling and Debt Management Agency (CCDM/ AKPK) can provide the financial education in the workplace to help them to be better informed in various aspects of finances that lead them to make better decisions. By understanding more about the determinants of financial wellbeing, it is hoped to help young employees to become financial prudence and in the long-run could decrease the number of young employees declared bankruptcy.